2020
DOI: 10.1111/epi.16667
|View full text |Cite
|
Sign up to set email alerts
|

Continuous EEG findings in patients with COVID‐19 infection admitted to a New York academic hospital system

Abstract: Objective: There is evidence for central nervous system complications of coronavirus disease 2019 (COVID-19) infection, including encephalopathy. Encephalopathy caused by or arising from seizures, especially nonconvulsive seizures (NCS), often requires electroencephalography (EEG) monitoring for diagnosis. The prevalence of seizures and other EEG abnormalities among COVID-19-infected patients is unknown. Methods: Medical records and EEG studies of patients hospitalized with confirmed COVID-19 infections over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 35 publications
8
80
2
1
Order By: Relevance
“…In addition, a previous spectral analysis study of the EEG confirmed the electrical changes in case of encephalopathy, even suggesting the ability to differentiate between infectious toxic encephalopathy on the one hand, and from encephalopathies in a context of severe hypoxia on the second hand (16). The proportion of altered EEG of about 85% reported here regardless the medical indication, was similar to those previously reported (15,17). Viral infection with COVID 19 in patients with epilepsy may trigger or worse epileptic seizures more easily, particularly in the case of genetic abnormalities (18).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, a previous spectral analysis study of the EEG confirmed the electrical changes in case of encephalopathy, even suggesting the ability to differentiate between infectious toxic encephalopathy on the one hand, and from encephalopathies in a context of severe hypoxia on the second hand (16). The proportion of altered EEG of about 85% reported here regardless the medical indication, was similar to those previously reported (15,17). Viral infection with COVID 19 in patients with epilepsy may trigger or worse epileptic seizures more easily, particularly in the case of genetic abnormalities (18).…”
Section: Discussionsupporting
confidence: 89%
“…One study reports nearly 41% of epileptiform abnormalities with 88% of frontals sharp waves. The proportion of EEG anomalies in favor of encephalopathy was 18% (14) for 21% in our study while Pellinen et al (15) reported moderated generalized slowing for 57%. In addition, a previous spectral analysis study of the EEG confirmed the electrical changes in case of encephalopathy, even suggesting the ability to differentiate between infectious toxic encephalopathy on the one hand, and from encephalopathies in a context of severe hypoxia on the second hand (16).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…These are not unexpected, because clinical seizures before EEG are associated with electrographic seizures on EEG, 12 and patients with prior neurologic injury are known to be at higher risk for nonconvulsive seizures. 9 Of note, the study by Pellinen and colleagues 19 also reported a suspected clinical seizure before EEG as a risk factor for electrographic seizures. Interestingly, in our study, the maximal fibrinogen level was inversely associated with the risk of seizures; this could reflect the possibility that COVID-19 provoked seizures in patients with epilepsy even in the absence of a significant systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described EEG results in patients affected by COVID-19 [26][27][28][29][30]. In most case series, EEG testing is performed following a seizure or altered consciousness, on suspicion of acute symptomatic seizures or encephalopathy [26][27][28][29]. Many of those reports have found no COVID-19-specific findings that would lead to suspicion of COVID-19 infection based on EEG testing [26][27][28].…”
Section: Eeg Findings In Patients With Covid-19mentioning
confidence: 99%